Non-State Actors and Election Management Practices in Nigeria: Issues and Way Forward - Salawu, Ibrahim O; Kolawole, Ayodele; Alfakoro, Abubakar S. Yushau (UUM Press, 2025)
Elections are a fundamental principle in any democratic setting. Notwithstanding, the electoral management process in Nigeria has been blighted with several anomalies and conspiracies. To strengthen the election management process, the roles of the non-state players seem essential in realizing these purposes. The primary objective of this study is to identify the institutional and legal framework available for non-state actor involvement in the election administration process in Nigeria’s Fourth Republic using the case study approach to probe into the operations of the Youth Initiative for Advocacy, Growth, and Advancement (YIAGA-Africa). This study adopted the primary and secondary research methods while the research design was qualitative. Primary data were obtained directly through the interviews, while journals, articles, textbooks, periodicals, and the internet formed the secondary basis. The total population for this study was one hundred and forty-seven (147) purposively sampled respondents. The qualitative data results were presented in thematic forms. The study revealed that, indeed, there exists a legal and institutional framework for non-state actors’ involvement in the election management process in Nigeria; however, this remains deficient as a palpable imbalance pervades the legal framework. The study recommends that the National Assembly work out modalities, make new laws, and address misconceptions in the institutional and legal framework for non-state actors to give them a smoother operational environment in the election management process